2019
DOI: 10.3168/jds.2018-16103
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum DR7 improved upper respiratory tract infections via enhancing immune and inflammatory parameters: A randomized, double-blind, placebo-controlled study

Abstract: The aims of this study were to investigate the effects of Lactobacillus plantarum DR7 isolated from bovine milk against upper respiratory tract infections (URTI) and elucidate the possible mechanisms underlying immunomodulatory properties. The DR7 strain (9 log cfu/d) was administered for 12 wk in a randomized, double-blind, and placebo-controlled human study involving 109 adults (DR7, n = 56; placebo, n = 53). Subjects were assessed for health conditions monthly via questionnaires, and blood samples were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 35 publications
0
55
0
Order By: Relevance
“…This is in contrast with the other metabolite of tryptophan and kynurenine, where an increased conversion to kynurenine from tryptophan has been reported to increase incidences of upper respiratory tract infections (URTI) [ 50 ]. We have previously reported the effects of DR7 on improving symptoms of URTI via modulating systemic immunity and inflammatory responses in adults [ 51 ]. Information on the effects of gut microbiota on the pathways of dopamine remains limited as compared to that of serotonin, where a decrease in serotonin level has been associated with the absence of certain gut bacteria in germ-free animals as early as 1967 [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is in contrast with the other metabolite of tryptophan and kynurenine, where an increased conversion to kynurenine from tryptophan has been reported to increase incidences of upper respiratory tract infections (URTI) [ 50 ]. We have previously reported the effects of DR7 on improving symptoms of URTI via modulating systemic immunity and inflammatory responses in adults [ 51 ]. Information on the effects of gut microbiota on the pathways of dopamine remains limited as compared to that of serotonin, where a decrease in serotonin level has been associated with the absence of certain gut bacteria in germ-free animals as early as 1967 [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lactobacillus administration can have the potential for improving immune reactivity. These were accompanied by enhancing CD + T celldendritic cell interactions, lymphocyte proliferation, and cytokine secretion (IL-1b, IL-6, IL-10, IL-12, IFN-g, and TNFa) in mucosal immunity in a recent study (73)(74)(75)(76). Lactobacillus can also produce lactic acid, which can be used as a precursor for butyric acid synthesis (77).…”
Section: Discussionmentioning
confidence: 98%
“…Levels of interferons, mucosal antibodies of lung and activity of NK cells, antigen presenting cells (APCs) are improved by probiotics (89). Lactobacillus plantarum DR7 strain has shown to have suppressing effect on the pro-inflammatory cytokines TNF-α, IFN-γ, enhances anti-inflammatory cytokines IL-10, IL-4 and also known to reduce plasma peroxidation levels as well as modulate immune system (90). It is reported that Lactobacillus acidophilus CMCC878 administration in mice infected with Staphylococcus aureus, and Pseudomonas aeruginosa decreased the damage in the lungs by reducing the bacterial load and reducing the inflammation (91).…”
Section: Probioticsmentioning
confidence: 99%